Heterologous expression of human VEGF165 in rat brain: dose-dependent, heterogeneous effects on CBF in relation to vascular density and cross-sectional area - Vogel, Johannes; Hörner, Christian; Haller, Christlieb; Kuschinsky, Wolfgang (Journal of cerebral blood flow & metabolism, 2003)
Vascular endothelial growth factor (VEGF) induces increased vessel permeability and formation of abnormal vessels. To investigate cerebral blood flow (CBF) during local overexpression of VEGF recombinant adenoviruses carrying the human VEGF165 complementary DNA (2.3 to 23 · 108 pfu/mL) were injected stereotactically into the caudate nucleus of anesthetized rats. Saline and adenoviruses carrying the β-galactosidase gene served as controls. Eleven days later (1) size and density of vessels were assessed in hematoxylin-eosin-stained sections, (2) vascular permeability was measured by intravenous Evans blue injections, and (3) local CBF (lCBF) was quantified using the iodo-[14C]antipyrine technique. Dose-dependent increases were found in (1) vessel density and size (only vessels >43 μm could be quantified morphologically), (2) Evans blue extravasation and brain edema formation, and (3) lCBF (up to eightfold). At medium doses, hyperemic areas and smaller areas of decreased lCBF were found. In low flow areas, vascular cross-sectional areas were increased 223-fold and vessel density up to 10-fold. In high flow areas, these parameters were increased 32-fold and up to 15-fold, respectively. Adenovirus mediated VEGF overexpression results in (1) increased vessel size and density, (2) areas of increased and of decreased flow, and (3) more and smaller vessels in high flow than in low flow areas. These results indicate a diverging flow pattern of newly formed vessels.